ANALYSIS OF THE COMMONLY PRESCRIBED ANALGESICS POST PERIODONTAL FLAP SURGERY - AN INSTITUTIONAL BASED RETROSPECTIVE STUDY - Harikrishnan, Reshma; Ganesh S, Balaji (International Journal of Psychosocial Rehabilitation, 2020)
Periodontal flap is a section of the gingiva and/or mucosa surgically separated from the underlying tissues to provide visibility and access to the bone and root surface. It is indicated in case of irregular bony contours, deep craters, deep pockets, furcation involvement, intrabony pockets, persistent inflammation. One of the main complications of flap surgery is pain. All dental procedures should reduce pain. Analgesics are prescribed to reduce pain and help ease the patient. These are a class of medication designed specifically to relieve pain. Some of which includes nonsteroidal anti-inflammatory drugs and Opioids. This study was performed with an aim to analyse the most preferred prescription of analgesics by dentists after performing a periodontal flap surgery. The present study was a retrospective study done in a university setting at the Department of Periodontology in a private dental college. The study involved all the patients who had undergone periodontal flap surgery in a given time frame. The time period was from June 2019 to April 2020. A total of 375 patients were included in the study. Parameters such as Age, Gender, Type of flap surgeries and Analgesics prescribed were taken into consideration. The data was sorted and imported into SPSS software for analysis. 60% of the patients in the study were male, 40% were females. 62.9% of the patients underwent localized flap surgery and 37.1% underwent full mouth flap surgery. The various analgesics that were prescribed to the patients included Zerodol SP (40%), Zerodol P (36.8%), Zerodol (10.1%), Imol (5.3%), Dolo 650 (1%) and Combi flam (7.5%). Most frequently prescribed being Zerodol SP and least preferred being Dolo 650. Association between the type of flap surgery and the analgesics prescribed were analyzed. It was found that Zerodol SP was prescribed more frequently in both localized and full mouth periodontal flap surgery cases (p value > 0.05 - statistically not significant). Thus, the most commonly prescribed analgesic following periodontal flap surgery was Zerodol SP [Aceclofenac 100mg+ Serratiopeptidase 15mg + Paracetamol 325mg].